Root resorption of maxillary incisors after en masse intrusion and retraction with controlled tipping versus bodily movement in adults - Mais Medhat Sadek (Journal of Orthodontic Science, 2023)
INTRODUCTION: The purpose of this study was to evaluate and compare the incidence of orthodontically induced inflammatory root resorption (OIIRR) after en masse maxillary incisors intrusion and retraction with controlled tipping versus bodily movement using cone beam computed tomography (CBCT). MATERIAL AND METHODS: This study is a retrospective study performed on CBCT scans of 36 adult females who had their maxillary first premolars extracted followed by en masse anterior retraction and intrusion using labial biocreative therapy type II. Subjects were divided into two groups of 18 subjects each based on the type of tooth movement required during en masse retraction: Group I; the controlled tipping group, and Group II; the bodily movement group. The amount of intrusion, crown and root retraction, change in incisor inclination, and difference in tooth length was measured from the CBCT scans. Independent t tests were used to compare the measurements between the two groups. Pearson rank correlation analysis was applied to identify the relationship between the mean dental changes and the mean changes in tooth length for all four upper incisors. RESULTS: OIIRR was found in all four maxillary incisors in both groups. No significant differences were found between the two groups. OIIRR was positively correlated to the amount of root apex retraction and negatively correlated to the change in incisor inclination. CONCLUSIONS: Anterior retraction and intrusion lead to obvious root resorption affecting all maxillary incisors. No significant differences were found between the two groups. Careful clinical monitoring is needed for patients requiring anterior retraction with intrusion with maximum anchorage.